TOWARDS A STANDARD SPECIFIC ENVIRONMENTAL ACCOUNTING: RECOGNITION AND COMPREHENSIVE MEASUREMENT INFORMATION - Choy Zevallos, Elsa Esther (2014)
The issue of environmental impact in the world, let’s admit the presence of the emergence of a new accoun-ting business and financial discipline, with changes in the conceptual framework and the specific rules that add value to traditional accounting information. This would involve the adoption of new measurement methods, estimates and conceptual update on assets, liabilities, expenses, costs and liabilities; with the particulars surrounding the “environment”, leading him to a more qualitative than quantitative analysis. A challenge for the accounting science and interference from other sciences, to provide more knowledge. There is no specific environmental accounting stan-dard before this vacuum, using certain existing rules are presenting a generic treatment for environmental situations such as: NIC 16, NIC 36, NIC 37 and NIC 38. The goal is to express the need to establish thefoundation for a conceptual framework and scope of the environmental standard, bases for recognition, measurement and disclosure, in order to achieve comprehensive accounting information. Currently, the issue is under investigation, which has a deductive descriptive methodological approach. In the end, we intend to present a structure of the foundations for an environmental framework.